Detrital zircon age and provenance constraints on late Paleozoic ice-sheet growth and dynamics in Western and Central Australia. Issue 2 (17th February 2019) - Martin, J. R.; Redfern, J.; Horstwood, M. S. A.; Mory, A. J.; Williams, B. P. J.
Abstract: U–Pb dating and Hf-isotope provenance analysis of detrital zircons from the glaciogenic lower Permian Grant Group of the Canning Basin indicate sources principally from basement terranes in central Australia, with subordinate components from terranes to the south and north. Integrating these data with field outcrop and subsurface evidence for ice sheets, including glacial valleys and striated pavements along the southern and northern margins of the basin, suggests that continental ice sheets extended over several Precambrian upland areas of western and central Australia during the late Paleozoic ice age (LPIA). The youngest zircons constrain the maximum age for contemporaneous ice sheet development to the late Carboniferous (Kasimovian), whereas palynology provides a minimum age of early Permian (Asselian–Sakmarian). Considering the palynological age of the Grant Group within the context of regional and global climate proxies, the main phase of continental ice sheet growth was possibly in the Ghzelian–Asselian. The presence of ice sheets older than Kasimovian in western and central Australia remains difficult to prove given a regional gap in deposition possibly covering the mid-Bashkirian to early Ghzelian within the main depocentres and even larger along basin margins, and the poor evidence for older Carboniferous glacial facies. There is also no evidence for extensive glacial facies younger than mid-Sakmarian in this region as opposed to eastern Australia where the youngest regional glacial phase was Guadalupian.